Preserving Organizational Memory Through the Externalization Process in Formal Organizations: A Systematic Literature Review - Ervina Nurjanah; Tamara Adriani Salim; Muhamad Prabu Wibowo (Counseling and Humanities Review, 2026)
This study examines the contribution of tacit knowledge externalization to the preservation of organizational memory and identifies the mechanisms and barriers that emerge within formal organizational contexts. The study applies a systematic literature review method using PRISMA 2020 as the reporting guideline for the literature selection process. Data were analyzed through a narrative synthesis approach to describe key findings from relevant studies. The results indicate that externalization plays a fundamental role in sustaining organizational memory by mitigating knowledge loss, strengthening collective memory, and developing knowledge repositories. Externalization mechanisms are identified in two main categories, consisting of process-based mechanisms and technology-based mechanisms. The most influential barriers to externalization are concentrated in three main clusters, namely cultural, structural, and technological factors, which simultaneously weaken organizational capacity to build and sustain collective memory in contemporary formal organizational settings. Overall, the findings emphasize that externalization depends on readiness to address barriers.